2000
DOI: 10.1089/152460900318966
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Medical Care among HIV-Positive Incarcerated Women: The Rhode Island Experience

Abstract: Our objective was to characterize the clinical presentation of human immunodeficiency virus (HIV) infection among incarcerated women in a program that provides HIV testing and primary care to all state prisoners in Rhode Island. A retrospective medical chart review on all HIV-seropositive women who were incarcerated between 1989 and 1994 and had at least two medical visits with an HIV medical care provider was used. At the Rhode Island Adult Correctional Institution (ACI), under mandatory testing laws between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
0
22
0
4
Order By: Relevance
“…9 While these individuals frequently lead chaotic lives, they are also intensively case managed in some U.S. jails and have access to social and medical resources both in and out of the institution. [10][11][12][13][14][15][16] Health-related efforts in correctional facilities have mainly focused on short-term (G3 years) risk reduction and interventions to improve continuity of care after release, and even effective programs to improve HIV outcomes on the inside have shown reversal of gains made after release to the community. 17 Risk reduction interventions have demonstrated positive outcomes related to behaviors, 18 but the effect of such interventions on decreasing recidivism has often been inconclusive or not measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 While these individuals frequently lead chaotic lives, they are also intensively case managed in some U.S. jails and have access to social and medical resources both in and out of the institution. [10][11][12][13][14][15][16] Health-related efforts in correctional facilities have mainly focused on short-term (G3 years) risk reduction and interventions to improve continuity of care after release, and even effective programs to improve HIV outcomes on the inside have shown reversal of gains made after release to the community. 17 Risk reduction interventions have demonstrated positive outcomes related to behaviors, 18 but the effect of such interventions on decreasing recidivism has often been inconclusive or not measured.…”
Section: Introductionmentioning
confidence: 99%
“…17 Risk reduction interventions have demonstrated positive outcomes related to behaviors, 18 but the effect of such interventions on decreasing recidivism has often been inconclusive or not measured. 10,11 Interventions to improve continuity of care and links to outside programs have demonstrated that high-risk individuals will access, utilize, and benefit from medical and social services provided by a regular network of providers, [12][13][14][15][16]19 but these have not been evaluated for their long-term effect on recidivism.…”
Section: Introductionmentioning
confidence: 99%
“…Because pretest counseling for HIV can be a barrier to expanded testing, the CDC initiative now promotes HIV testing that does not require pretest counseling. 2 Correctional systems represent important sites for the detection of HIV [3][4][5] ; they house the nation's highest concentration of HIV-infected individuals. 6 For example, in 2000, 2.2% of all inmates in US prisons and 5.2% of all inmates in the Northeast were HIV infected.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][23][24][25] Addictions to drugs and alcohol have been identified as key variables in the propagation of such risks, and an array of prison-based and postincarceration intervention models have been developed and are being evaluated. 19,[26][27][28] It is crucial to determine ways to reduce HIV risk behaviors among incarcerated women returning to the community. Lower educational attainment has been reported as a risk factor for higher rates of HIV risk behavior among female inmates, although evaluation of different educational factors has not been conducted.…”
Section: Introductionmentioning
confidence: 99%